Clinical and etiological profile of heart failure - Mistry, Bansari S.; Pathak, Krupa; Trivedi, Smita K. (International Journal of Advances in Medicine, 2019)
Background: The overall prevalence of heart failure (HF) is thought to be increasing, in part because current therapies for cardiac disorders such as myocardial infarction (MI), valvular heart disease and arrhythmias, are allowing patients to survive longer. Aims of the study were to know the presentation, causes, outcome of HF patients and to know the proportion of patients with heart failure with preserved ejection fraction (HFpEF) and heart failure with reduced ejection fraction (HFrEF). Methods: This was a cross-sectional observational study of heart failure patients for duration of one year, admitted in medicine department of medical college and SSG hospital, Vadodara, Gujarat, India. Results: Males constituted more than half of patients; however, HFpEF was more common in females in all age groups. Majority of patients had HFrEF. Breathlessness was the common presenting symptom. Common aetiologies found were ischaemic heart disease (IHD), hypertension (HTN), diabetes mellitus (DM) and valvular heart disease. 50-64 year patients constituted the major age group. IHD and DM were more common in this age group. Rheumatic heart disease (RHD) was seen commonly in 20-34 year of age group. In-hospital mortality rate though low has not much changed and contributes significantly considering the prevalence. Conclusions: Like developing countries, IHD contributes a major portion of patients with HF with risk factors like DM and HTN. Though, the contribution from RHD still cannot be ignored. There is little decrease in mortality but considering prevalence the burden is still high.